Factors determining nurses' knowledge of evidence-based pressure ulcer prevention practices in Finland: a correlational cross-sectional study - Parisod Heidi; Holopainen Arja; Koivunen Marita; Puukka Pauli; Haavisto Elina (Wiley, 2025)
Background Pressure ulcers cause economic burden, human suffering, pain and decreased health-related quality of life in patients. Pressure ulcers are preventable in most cases, and nursing staff knowledge is a key factor in successful pressure ulcer prevention. Further evidence is needed to better tailor pressure ulcer prevention training programmes to the nursing staff.
Aim To evaluate the level of nursing staff knowledge about evidence-based pressure ulcer prevention practices in both primary and specialised care, and to identify what factors determine nurses' knowledge levels.
Methods A correlational, cross-sectional study was conducted from 2018 to 2019 in two hospital districts in Finland. The Pressure Ulcer Prevention Knowledge test was used to collect data, and the Attitude towards Pressure ulcer Prevention (APuP) instrument was used as a background variable. The data were statistically analysed with Wilcoxon and Kruskal-Wallis tests, Spearman correlations and multiple linear regression.
Results The pressure ulcer prevention knowledge of the participating registered nurses, practical nurses and ward managers (N = 554) was on average 24.40 (max. 35.00). There was no difference in the participants' knowledge based on the type of unit in which they were working (primary or specialised care). The participants' attitudes (p < 0.0001), current position (p = 0.0042), frequency of taking care of patients with pressure ulcers (p = 0.0001) and self-evaluated training needs (p < 0.0001) independently explained the variation in the knowledge scores.
Conclusions Special attention needs to be paid to the knowledge of those nurses working in positions that require lower levels of education and those who rarely take care of patients with pressure ulcers. Supporting nurses' positive attitudes towards pressure ulcer prevention should be an essential part of pressure ulcer prevention training. Nurses' self-evaluations of their training needs can be used to target training. The limitations of the study should be considered when generalising the results.